If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = x + -2 Reorder the terms: -16 = -2 + x Solving -16 = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -16 + -1x = -2 + x + -1x Combine like terms: x + -1x = 0 -16 + -1x = -2 + 0 -16 + -1x = -2 Add '16' to each side of the equation. -16 + 16 + -1x = -2 + 16 Combine like terms: -16 + 16 = 0 0 + -1x = -2 + 16 -1x = -2 + 16 Combine like terms: -2 + 16 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14
| 24y+2x=48 | | 25(3)-5y=-25 | | 45x-24= | | 4x-104=180 | | 8-40=4a+60 | | 3r/1=4 | | 1.25q-12.5=8.35 | | -29b-84=b+336 | | b+11*3=-2 | | -8=4(y+1) | | (3x-8)(2x-4)= | | (-n+(-5))-(6n+(-6))= | | 8-15P=3P-10 | | 25x-5y=-25 | | 2.5x-6=-4-3.5x | | 14=x+-4+2x | | f=.50kv | | 4x-14=180 | | 9n^2=44n | | (3n+5(-5))-(2n+(-8))= | | f(x)=x^3-3x^2+3x-1 | | ln(x+1)=1.2+ln(x) | | -9=-5y+6 | | 74x=257+(-63x) | | 4u+4-54=14 | | 12=6y+12x | | 7x^2=74x | | 4u+4-54=-14 | | 5=4t+13 | | 3(2n-1)=6n-4 | | x^4+14x^2+48=0 | | X^2-12x+210=0 |